Effect of Benzyl Amino Purine (BAP) on the Leaf Growth of Vanda limbata Blume Orchid In Vivo - Sischa Aulia Putri Az Zahra; Nintya Setiari; Yulita Nurchayati (Universitas Sebelas Maret, 2024)
Vanda limbata is a natural orchid with slow growth and is often taken directly from the forest in large quantities, threatening its sustainability. Ex-situ preservation efforts are needed for this orchid, one of which is through cultivation with the addition of Benzyl Amino Purin (BAP), known to increase shoot growth. This research aims to analyze the effect of BAP and determine its optimal concentration on the growth of V. limbata orchids. This research used a single-factor completely randomized design in BAP concentrations of 0, 25 and 50 mg l-1 with 5 replications. The method used was spraying BAP solution once a week on all parts of adult V. limbata orchids aged ±2 years. The research was conducted for 3 months in the experimental garden with parameters observed in the form of the number of new leaves, elongation of old leaves, the length of new leaves, increase in the width of old leaves, the width of new leaves, stomatal density and the number of roots. The results showed that the most effective BAP concentration was 50 mg l-1 for the number of new leaves which increased by 200%, the length of old leaves which increased by 168.66% and the length of new leaves which increased by 800%, but resulted in less stomatal density than the control. BAP can increase the growth of V. limbata orchid leaves. This research can be a recommendation for ex-situ conservation efforts that have the potential to be developed as a means of orchid cultivation.